Kesiapan Mahasiswa Program Studi Pendidikan Matematika Dalam Menempuh Mata Kuliah Magang 3 Di Smk Negeri 9 Surakarta Tahun 2015/2016 - Aditya, Nuril I'isnaini Mega, Rita P. Khotimah, S. Si., M. Sc (2017)
This research has purpose to describe the preparation of students of math program education to reach lecture of apprenticeship 3 in SMK negeri 9 Surakarta in academic year of 2015/2016. This kind of research is describe qualitative. The subject of this research are the student of math program education of FKIP UMS and the teachers from SMK negeri 9 Surakarta. The technique to collecting the data are with interview and documents. The analysis technique that be used are the analysis model of miles and huberman. The data use source of triangulation and technique. The result of the research show that mostly of the student of math program education of FKIP UMS was preparation professional competence, pedagogue competence, social competence, and personal competence for apprenticeship 3 in SMK negeri 9 surakarta in academic year of 2015/2016. Student mastery of material indicated readiness to consider the importance of preparing the material before teaching and student efforts seeking reference material taught. Readiness of pedagogical competence demonstrated by the importance of making a lesson plan before teaching, select approopriate leearning method, using appropriate instructional media, and evaluating learning. Social competence demonstrated readiness of students to obey school rules, seeks to always be responsible and behave properly teacher. Personal competence demonstrated to be mature and act in a manner. Keyword: preparation, apprenticeship 3, students.